Factors influencing travel behavior and their potential solution : a review of current literatures - Mohd. Shariff, Norhazlin; Shah, Muhammad Zaly (Faculty of Built Environment, UTM, 2008)
Traffic congestion in metropolitan areas has developed into a major problem in many countries all over the world. They have a negative impact on the economy, the environment and the overall quality of life. Time-delay, pollution, land user and stress are some of the impact that appear from congestion. This paper presents an overview of current literatures on the factors that fluence travel behavior as well their impact. Also, potential solutions to this problem are provided which represent the current thinking of transportation planners in mitigating the adverse impact of motorized traffic to socio-politic well-economic affected countries.